Karakterisistik Ekstrak Etanol 96% Kulit Jeruk Purut, Analisa GCMS dan Penetapan Nilai SPF (Sun Protection Factor) - Dewi Rahma Fitri; Nespi Leo Renzi; Triana Triana; In Rahmi Fatria Fajar; Iin Hardiyati (LPPM Universitas Abdurrab, 2024)
Exposure to high intensity ultraviolet light can cause sunburn, erythema, and tanning. In addition, ultraviolet radiation encourages the formation of ROS (reactive oxygen species) and nitrogen species (RNS), resulting in skin damage. To prevent this, antioxidants are needed which function to protect the skin from the bad effects of ultraviolet rays. Kaffir lime or what is commonly called kaffir lime has the potential to be a rich source of bioactive compounds. Kaffir lime peel contains essential oil components such as linalool, citronellol, geraniol, citronellal, and other components that have antioxidant activity. The aim of this research was to determine the characteristics of 96% ethanol extract of kaffir lime peel, chemical content and determine the SPF value. Kaffir lime peel was extracted using 96% ethanol and tested for extract characteristics, GCMS analysis and SPF value tested using the Mansur method. The results of the extract characteristics test showed a yield of 8.22%, air content of 8.74%, ash content of 2.17% and drying loss of 1.3%. Phytochemical screening showed results containing tannins, alkaloids and flavonoids and secondary metabolite compounds, GC-MS analysis showed the compounds beta-mycrene, gamma terpinene, linalool, terpinen-4-ol, geraniol, caryophyllene, nerolidol, sphatulenol, citronellal and Neral. SPF test results at a wavelength of 290-320nm with a concentration of 100 ppm: 23.096271, 150 ppm: 35.833618, 200 ppm: 45.047732, 250 ppm: 56.55952, 300 ppm: 68.919985